Evaluation of ARFI elastography for detecting active mastitis in sheep with previous fibrous lesions: a study of mammary parenchyma and supramammary lymph nodes - da Silva Bonacin, Yuri [UNESP]; Santos, Victor José Correia [UNESP]; Maronezi, Marjury Cristina [UNESP]; Aires, Luiz Paulo Nogueira [UNESP]; Machado, Michele Pereira; Barbosa, Beatriz Longo; Santana, André Marcos; Del’Aguila-Silva, Priscila [UNESP]; Canola, Paulo Aléscio [UNESP]; Feliciano, Marcus Antônio Rossi [UNESP]; Marques, José Antônio [UNESP] (FapUNIFESP (SciELO), 2024)
The aim of the study was to evaluate the use of Acustic Radiation Force Impulse (ARFI) elastography in mammary parenchyma and supramammary lymph nodes, for detection of active mastitis in sheep with naturally infected chronic fibrous lesions. 27 female sheep were included and B-mode ultrasound and ARFI elastography images were obtained, acquiring qualitative (echogenicity and echotexture) and quantitative (shear rate, depth and short/long axis ratio) variables of 48 mammary glands. The glands were divided into three experimental groups: control group (CG) - healthy animals; LSCC- animals that presented fibrous lesions and SCC (somatic cell count) less than 500 x 103 cls/mL; HSCC: animals that presented fibrous lesions and SCC (somatic cell count) more than 500 x 103 cls/mL; The qualitative variables using B-mode ultrasonography, including echotexture and echogenicity, showed no significant differences between the evaluated groups and tissues (p = 0.9336 and p = 0.233, respectively).In healthy areas of the gland, it was an increasing in shear wave velocity (SWV) in LSCC than in HSCC (p=0.04). When comparing the fibrosis in the LSCC and HSCC groups with their respective normal areas, the velocity increased in both groups: LSCC (p= 0,0007) and HSCC (p= 0,0001). When comparing the areas of fibrosis in LSCC and HSCC with the CG parenchyma, there was an increase in LSCC (p=0.001) and HSCC (p=0.0001). B-mode ultrasound indicate predominance of hypoechoic echogenicity in lymph nodes and reduced short/long axis ratio in cases of active subclinical mastitis. The supramammary lymph node showed increased SWV when comparing the CG with HSCC groups (p=0.02) and GC with LSCC (p=0.04). B-mode ultrasonography is useful for evaluating the mammary parenchyma, however, its application as a standalone diagnostic technique is not recommended. ARFI elastography indicates potential cutoff points for differentiating subclinical mastitis from healed mastitis, highlighting its importance as a tool for distinguishing normal areas from fibrous parenchymal areas. While this study did not establish specific cutoff points due to sample size limitations, further research with larger sample sizes could explore and define these critical thresholds.
Keywords: Inflammation; milk; sheep; ultrasound